Assessing the Practice of Hot Spots Policing: Survey Results From a National Convenience Sample of Local Police Agencies. (May 2014) - Koper, Christopher S.
This study examined the practice of hot spots policing as reported by a convenience sample of predominantly large municipal police agencies. Police commonly defined hot spots in terms of micro places as well as larger areas, and they emphasized short-term identification and responses to hot spots. Respondents identified problem analysis/solving, targeting offenders, and directed patrol as the most common and effective strategies for hot spots, but there was wide variation in their views of the most effective strategies for different types of hot spots. Current practices could arguably be improved through more a precise geographic focus, a greater emphasis on chronic hot spots and their criminogenic features, and further research to determine optimal strategies, dosages, and proactive uses of hot spots policing.